The Influence of Ethnophysics Flipbook Media on the Learning Outcomes of High School Students on Temperature and Heat Materials - Hasanah, Atiqotul; Mahardika, I Ketut; Ernasari, Ernasari (International Journal of Education, Information Technology, and Others, 2025)
Physics learning in schools in general is still centered on the material available in books. But there is very little learning about physics that really relates to the culture that exists in the student environment. The purpose of this study is to examine the influence of the use of ethnophysics flipbook media on student learning outcomes. This study is a quasi-experimental research using a non-equivalent control group design. This research was carried out in the even semester of the 2024/2025 school year, precisely at SMAN Kalisat. Sample selection was carried out by a homogeneous testing method, selected by lot to obtain control and experimental classes. Based on the results of the normality test, the Sig. value obtained is 0.000 where the value is < 0.05 so that the data is not distributed normally. Then it was followed by the Mann-Whitney U test because the data was abnormal. The results of the Mann-Whitney U Non-Paramentric test showed that the significant values obtained were 0.000 < 0.05. So it can be concluded that the use of ethnographic flipbook media has an effect on the learning outcomes of high school students on Temperature and Heat material.